Optimizing cardiometabolic risk in people living with human immunodeficiency virus: A deep dive into an important risk enhancer - Elizabeth A. Kobe; Aarti Thakkar; Sarina Matai; Esra Akkaya; Neha J. Pagidipati; Robert W. McGarrah; Gerald S. Bloomfield; Nishant P. Shah (Elsevier, 2024)
Effective antiretroviral therapy (ART) is now nearly ubiquitous. However, the survival benefits conferred with ART contribute to an aging human immunodeficiency virus (HIV) population and increased risk of chronic diseases, like atherosclerotic cardiovascular disease (ASCVD). Furthermore, HIV is a known risk enhancer of ASCVD and acknowledged as such in the current 2018 AHA/ACC Blood Cholesterol guidelines [1]. This makes cardiovascular risk factor identification and modification among people living with HIV (PLWH) of increasing importance to prevent cardiovascular events. In this review, we aim to summarize the epidemiology and pathogenesis of how HIV is linked to atherogenesis and to discuss cardiometabolic risk factor modification specific to PLWH, covering obesity, hypertension, insulin resistance, metabolic dysfunction-associated steatotic liver disease, and dyslipidemia.